THE ANALYSIS OF FUNCTION AND MEANING BEHIND THE TRADITIONAL ELDERS’ PERCEPTION AND ROLE IN SOLO HULIR SE’ANG HALA AS PART OF THE DISPUTE - Gobang, Yonas Klemens Gregorius Dori; Eni, Genoveva Dua (Jurnal Review Pendidikan dan Pengajaran, 2025)
This research analysed the function and meaning behind traditional elders’ perceptions and roles in solo hulir se’ang hala; a customary dispute resolution process, the role of traditional elders as negotiators in language conflicts that may occur, and the central role of traditional elders in interpreting every verbal and non-verbal activity. Conducted in Habi and Langir Villages, Sikka Regency, the study adopts a descriptive qualitative method within an ethnolinguistic framework. Traditional elders (’ata du’a mo’an) from these villages provided insights through observations and interviews. Solo hulir se’ang hala, equivalent to “insulting others” in the local language, encompasses actions like presumptuous speech, gossip, or slander, leading to communal disputes addressed by traditional elders. Offenders receive customary fines, including advice, guidance, and obligations to pay sanctions, to prevent recurrence. Each type of offensive speech incurs specific fines, acknowledging the wrong (haput wae meang). The resolution of disputes culminates in the Pati Wawi Perang Pare ritual, involving the communal slaughter of a pig and cooking of rice. The ceremony incorporates various language functions—expressive, informative, and directive—and meanings—connotative, social, and affective or emotive. This study highlighted the integral role of traditional elders in maintaining social harmony through customary rituals and language use.